A highly sensitive fluorescent chemosensor for simultaneous determination of Ag(I), Hg(II), and Cu(II) ions - Quang, Duong Tuan; Hien, Nguyen Khoa; Ai Nhung, Nguyen Thi; Trung, Nguyen Tien; Bao, Nguyen Chi; Diem Tran, Pham Thi (Vietnam Journal of Chemistry, 2015)
Simultaneous determination of the heavy metal ions at the µg/L level in an aqueous solution has always been attractive to scientists. Here, we present a simple, rapid and highly sensitive fluorescent chemosensor for simultaneous determination of mercury, copper, and silver ions in an aqueous solution in the presence of various competitive metal ions, including Na+, K+, Ca2+, Ba2+, Mg2+, Pb2+, Cd2+, Co2+, Zn2+, Fe2+, Ni2+, Al3+, and Cr3+ ions. The detection limits of the sensor for Hg2+, Cu2+, and Ag+ ions are 2.8, 0.8, and 1.0µg/L, respectively. This sensor is potentially suitable for detecting and monitoring these metal ions in drinking water samples according to the regulations of the World Health Organization.